Economic impact of the use of patiromer in chronic kidney disease or heart failure for the treatment of chronic hyperkalemia in Spain - Patricia de Sequera; Ramón Bover; Yoana Ivanova-Markova; Alexandra Ivanova; Almudena González-Domínguez; Marta Valls; Verónica Campos (Nefrología (English Edition), 2023)
Introduction: Chronic hyperkalemia has negative consequences in the medium and long term, and determines the suspension of nephro and cardioprotective drugs, such as renin–angiotensin–aldosterone system inhibitors (RAASi). There is an alternative to the suspension or dose reduction of these treatments: the administration of potassium chelators. The aim of this study is to estimate the economic impact of the use of patiromer in patients with chronic kidney disease (CKD) or heart failure (HF) and hyperkalemia in Spain. Materials and method: The annual economic impact of the use of patiromer has been estimated from the perspective of the Spanish society. Two scenarios were compared: patients with CKD or HF and hyperkalemia treated with and without patiromer. The costs have been updated to 2020 euros, using the Health Consumer Price Index. Direct healthcare costs related to the use of resources (treatment with RAASi, CKD progression, cardiovascular events and hospitalization due to hyperkalemia), direct non-healthcare costs (informal care: costs derived from time dedicated by patient’s relatives), the indirect costs (productivity loss), as well as an intangible cost (due to premature mortality) were considered. A deterministic sensitivity analysis was performed to validate the robustness of the study results. Results: The mean annual cost per patient in the scenario without patiromer is €9,834.09 and €10,739.37 in CKD and HF, respectively. The use of patiromer would lead to cost savings of over 30% in both diseases. The greatest savings in CKD come from the delay in the progression of CKD. While in the case of HF, 80.1% of these savings come from premature mortality reduction. The sensitivity analyses carried out show the robustness of the results, obtaining savings in all cases. Conclusions: The incorporation of patiromer allows better control of hyperkalemia and, as a consequence, maintain treatment with RAASi in patients with CKD or HF. This would generate a 32% of annual savings in Spain (€3,127 in CKD; €3,466 in HF). The results support the positive contribution of patiromer to health cost in patients with only CKD or in patients with only HF. Resumen: Introducción: La hiperpotasemia crónica tiene consecuencias negativas a medio y largo plazo, condicionando generalmente la suspensión de fármacos nefro y cardioprotectores, en pacientes con enfermedad renal crónica (ERC) e insuficiencia cardíaca (IC), como son los inhibidores del sistema renina-angiotensina-aldosterona. Existe una alternativa a la suspensión o reducción de dosis de estos tratamientos y es la administración de quelantes del potasio. El objetivo de este estudio es estimar el impacto económico que supondría el uso de patiromer en pacientes con ERC o IC e hiperpotasemia en España. Material y métodos: Se ha estimado el impacto económico anual del uso de patiromer desde la perspectiva de la sociedad española, comparando 2 escenarios: pacientes con ERC o IC e hiperpotasemia tratada con patiromer y sin patiromer. Los costes se han actualizado a euros de 2020, utilizando el índice de precios de consumo de Sanidad. Se han considerado los costes directos sanitarios relacionados con el uso de recursos (el tratamiento con inhibidores del sistema renina-angiotensina-aldosterona, la progresión de la ERC, los eventos cardiovasculares y la hospitalización por hiperpotasemia), los costes directos no sanitarios (cuidados informales: costes derivados del tiempo de dedicación por parte de los familiares del paciente), los costes indirectos (pérdidas de productividad laboral), así como un coste intangible (por mortalidad prematura). Se realizó un análisis de sensibilidad determinístico para validar la consistencia de los resultados del estudio. Resultados: El coste medio anual por paciente en el escenario sin patiromer es de 9.834,09 y 10.739,37 € en ERC e IC, respectivamente. El uso de patiromer supondría un ahorro de costes superior al 30% en ambas enfermedades. En el caso de la ERC, el mayor ahorro procede del retraso de la progresión de la ERC. Mientras que en IC el 80,1% de estos ahorros provienen de la reducción de la mortalidad prematura. Los análisis de sensibilidad realizados muestran la consistencia de los resultados, obteniendo ahorros en todos los casos. Conclusiones: La incorporación de patiromer permite controlar la hiperpotasemia y, como consecuencia, mantener el tratamiento con inhibidores del sistema renina-angiotensina-aldosterona en los pacientes con ERC o IC, generando unos ahorros anuales en España del 32% (3.127 € en ERC; 3.466 € en IC). Estos resultados apoyan la contribución positiva que patiromer puede tener tanto en los pacientes con ERC como en aquellos que solo tienen IC.